Cooperative employee performance analysis in Pekanbaru City - Arif Rahman; Saipul Al Sukri; Irsyad Kamal; Sonia Sischa Eka Putri; Asepma Hygi Prihastuti (Faculty of Economics and Business Mulawarman University, 2022)
This study aims to determine the effect of motivation, job satisfaction, work discipline on performance. The method used in this research is descriptive statistics. Data analysis used linear regression with the help of SPSS 22.0. The population in this study are those who work as employees in cooperatives in the city of Pekanbaru. Data were collected using a Likert scale. The number of samples was determined by the slovin method with consideration of a sample of 100 people. A total of 92 questionnaires were returned. The findings of this study indicate that employee motivation has a positive effect on employee performance, while job satisfaction and work discipline do not have a positive effect on employee performance. The final result of employee performance variables is influenced by motivation, job satisfaction and work discipline by 69.8%, while the remaining 31.2% is influenced by other variables outside of this study.